TRANSLATION OF CONCEPTUAL METAPHOR IN THE LEGAL DISCOURSE OF EU WHITE PAPERS - Gražytė, Rasa; Maskaliūnienė, Nijolė (Vertimo studijos, 2017)
Traditionally legal discourse has been perceived as an area of human activity where every attempt is made to speak or write precisely, clearly and unambiguously—i.e. no room is left for figurative language. In this context the use of metaphor is naturally unacceptable. With the change in the approach to metaphor as a mental phenomenon, rather than a language phenomenon or a means of embellishing the text, the study of metaphor in various types of discourse has received a new impetus. This article addresses the issue of conceptual metaphor translation in the legal discourse of EU White Papers. Metaphorical expressions are categorized into cognitive domains such as dealing with a problem is war, a problem is an enemy, responsibility is a burden, progress is a motion forward, etc. The analysis confirms the hypothesis that if metaphorical expressions exploit the same cognitive domain both in English and Lithuanian, metaphoricity is fully preserved in translation. Where cognitive domains differ, metaphoricity manifests itself in a different domain or is lost altogether.